A modeling investigation of ground and surface water fluxes for Konza Tallgrass Prairie - Lauwo, Simon Yesse (Kansas State University, 2007)
Konza Prairie is one of the few areas in the United States were natural landscape of the area is still intact. Human action on changing the landscapes in this area is limited and much of the land remains as native grassland. In spite of its natural existence, this area is not completely isolated from the rest of the world. Changes that are taking place in climate will eventually have the same effect to this region as well as other human populated areas. Increase in carbon concentration in the air has resulted to increase in temperature, this increase in temperature increases the evaporation from the sea, oceans and the ice capes. As the atmospheric water vapor changes the precipitation pattern also change. Changes in precipitation due to climate change will result to change in hydrology and hydraulics of the streams and groundwater flow regime. Precipitation provides surface runoff and groundwater infiltration, which recharge the cracked limestone aquifer present in the Konza area. The infiltration water moves trough the cracked rocks and eventually reach the creeks such as Kings Creek and flow to the Kansas River. Increase in precipitation will result to increase in surface runoffs and more groundwater recharge. Decrease in precipitation will result to decrease in both surface and groundwater. To examine changes in groundwater elevation as recharge change in Konza, a groundwater model was developed based on erosion impact calculator (EPIC) ecological model and SLIT groundwater model. EPIC model estimates the deep percolation (recharge) as 12% and total runoff to about 24% of the annual average precipitation. The annual average recharge values from EPIC were used in SPLIT to simulate results for the groundwater elevation at Konza prairie. Field wells elevation were use to calibrate the SPLIT results. By estimating the hydraulic permeability value to 0.546m/d the field well measurements and SPLIT simulated groundwater elevation results provide a good match. After calibration max and min recharge together with a 5-years moving average were used to examine the changes in groundwater elevation as recharge changes. Future study intends to use the calibrated Konza groundwater model and the forecasted climate data to simulate result for groundwater elevation as climate changes.
Keywords: Groundwater; Modeling; Analitic Element Method; Konza; Recharge; Tallgrass Prairie; Agriculture, Range Management (0777); Engineering, Civil (0543)